Fascioliasis in schoolchildren in the inter andean valley of Cajamarca, Peru - Rodríguez Ulloa, Claudia Rivera-Jacinto, Marco Hobán Vergara, Cristian Del Valle Mendoza, Juana Mercedes Ortiz Oblitas, Pedro (2015)
Fascioliasis, caused by Fasciola hepatica, is a public health problem in Peru, especially in schoolchildren. Prevalence rates in livestock are over 80% in dairy cattle reared in the Andean valley of Cajamarca, Peru. The present investigation aimed to determine the prevalence of F. hepatica infection in schoolchildren and the main risk factors involved in its presentation. Two hundred and seventy schoolchildren nine years old and over from primary public institutions from the district of Los Baños del Inca (Cajamarca) were included in the investigation. Questionnaires were applied to parents and children and fecal samples were taken and evaluated using the rapid sedimentation technique. Blood samples were also collected and analyzed. Seventeen fecal samples were positive to F. hepatica eggs, giving a prevalence of 6.3% (95% CI 3.21 - 9.38). Significant differences were found with origin of the child, history of intestinal parasitism, and the habit of chewing grass (p< 0.05). The rural origin (OR 4.8, 95% CI: 1.53-15.08) and the habit of chewing grass (OR 3.26, CI: 95% 1.07 - 9.96) were the most likely risk factors associated with the acquisition of infection. The leukocyte count of infected children varied between 3900 and 10580 cells /mm3 (mean ± SD = 6458.3 ± 2080.3). Thirty three percent of children positive to F. hepatica eggs presented eosinophilia. We conclude that the prevalence of human fascioliasis in the district of Los Baños del Inca is at the mesoendemic level and rurality provides conditions for acquiring the infection.